Lumbar Epidural Varix Mimicking Perineural Cyst - Pusat, Serhat (Korean Society of Spine Surgery, 2013)
Lumbar epidural varices are rare and usually mimick lumbar disc herniations. Back pain and radiculopathy are the main symptoms of lumbar epidural varices. Perineural cysts are radiologically different lesions and should not be confused with epidural varix. A 36-year-old male patient presented to us with right leg pain. The magnetic resonance imaging revealed a cystic lesion at S1 level that was compressing the right root, and was interpreted as a perineural cyst. The patient underwent surgery via right L5 and S1 hemilaminectomy, and the lesion was coagulated and removed. The histopathological diagnosis was epidural varix. The patient was clinically improved and the follow-up magnetic resonance imaging showed the absence of the lesion. Lumbar epidural varix should be kept in mind in the differential diagnosis of the cystic lesions which compress the spinal roots.